CEPHEIDS AS DISTANCE INDICATORS: SOME CURRENT PROBLEMS - Feast, M. (Одеські астрономічні публікації, 2017)
A general review is given of the calibration of the Cepheid distance scale, with particular reference to its use in the determination of H0. Emphasis is placed on the advantage of using a galactic calibration of the Cepheid scale, rather than relying on an adopted distance to the LMC. It is then possible to use LMC data to test for possible metallicity effects on this scale.